Adolescents' mental health and maladaptive behaviors before the Covid-19 pandemic and 1-year after: analysis of trajectories over time and associated factors - Laura Pedrini; Serena Meloni; Mariangela Lanfredi; Clarissa Ferrari; Andrea Geviti; Annamaria Cattaneo; Roberta Rossi (BMC, 2022)
Abstract Background Adolescents have been deeply exposed to negative consequences of social distancing imposed by Covid-19. There is a lack of longitudinal studies regarding the impact on adolescents of this unfavorable condition, and their results are controversial. The aim of the present prospective study is to assess psychopathological symptoms in adolescent students over time and to evaluate what type of impact the Covid-19 pandemic had on adolescents. Moreover, the association between mental health indexes, potential risk and resilience factors is explored. Methods Psychopathological symptoms (i.e., anxiety, depression, stress, emotional dysregulation, maladaptive behaviours), and potential risk and resilience factors (i.e., childhood trauma, emotional regulation skills, family function, personality traits) were assessed among a sample of 153 students (72% female; mean age 16.1 ± 0.49), living in a medium-size city in the north of Italy, at two time points: before the outbreak of the Covid-19 pandemic (November 2019-January 2020) and 1 year later (April-May 2021). Results After 1 year, we found an increase in mean scores on anxiety, stress for future uncertainty, and higher frequency of maladaptive behaviours. By contrast, the level of stress related to social domains (i.e., school attendance, romantic relationships, peer pressure) decreased. Dysfunctional emotional regulation skills, childhood trauma, low family functioning, and specific personality traits were associated to higher psychopathological symptoms. Cluster analysis detected three groups of youths based on their change over time in psychopathological symptoms: those who worsened (N = 23; 15%), improved (N = 55; 34%), or remained stable (N = 75; 46%). After controlling for baseline mental health status, those adolescents reporting increase in self-harm (OR = 2.61; p < 0.001), binge-drinking (OR = 3.0; p = 0.007), aggressiveness (OR 1.92; p = 0.004), and binge-eating (OR 2.55; p = 0.003) were more likely to present a worsened mental health condition. Conclusion The present results suggest that the Covid-19 pandemic seems to have had a different impact on subgroups of students. Indeed, we found a global worsening of psychological well-being only in a subgroup of adolescents, otherwise other students remained stable or improved. Increased frequency of maladaptive behaviors was found as a predictor of worsened mental health, therefore interventions to strengthen emotional regulation strategies are warranted. Finally, the decrease of stress in social domains could be due to reduction of potential triggering situations, thus indicating only a temporary beneficial effect that requires careful monitoring.